Organizational Behavior of KUD Tani in Tambang Emas Village: Facing Competition and Business Development - Etty Ramayani; Mayasari; Muazza; Ahmad Rifki (Indonesian Scientific Publication, 2026)
Organizational behavior is the result of complex interactions between individuals within an organization and is an important factor in determining the dynamics and sustainability of the organization. This study aims to identify and understand organizational behavior in the Tani Village Unit Cooperative (KUD) in Tambang Emas Village, South Pamenang District, Merangin Regency in facing competition and the efforts made to develop its business. This study uses a qualitative approach with a phenomenological design to explore the experiences and perspectives of the management. There were four informants, consisting of the Chair, Secretary, Treasurer, and Supervisor of the Cooperative. Data were collected through participatory observation, in-depth interviews, document studies, and documentation. Data analysis used an interactive analysis model that included data collection, data reduction, data presentation, and verification of findings. The results of the study show that KUD Tani experienced a significant decline in capital due to high member receivables and declining member trust in management, while pressure from external competitors further worsened business conditions. To overcome these problems, KUD Tani formed a special collection team, improved service quality, implemented competitive pricing strategies, and modernized its business and product innovation to strengthen member engagement. The implications of this study indicate that improving the credibility of management, strengthening financial management systems, and developing responsive service strategies are key to improving organizational performance and enhancing the competitiveness of KUDs amid increasingly fierce business competition.